2019
DOI: 10.3390/ijms20194757
|View full text |Cite
|
Sign up to set email alerts
|

APP, PSEN1, and PSEN2 Mutations in Asian Patients with Early-Onset Alzheimer Disease

Abstract: The number of patients with Alzheimer’s disease (AD) is rapidly increasing in Asia. Mutations in the amyloid protein precursor (APP), presenilin-1 (PSEN1), and presenilin-2 (PSEN2) genes can cause autosomal dominant forms of early-onset AD (EOAD). Although these genes have been extensively studied, variant classification remains a challenge, highlighting the need to colligate mutations across populations. In this study, we performed a genetic screening for mutations in the APP, PSEN1, and PSEN2 genes in 200 cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 92 publications
(132 reference statements)
1
25
0
2
Order By: Relevance
“…Our re-analysis found that most PSEN1 variants are located in exon 7, exon 5, exon 8, exon 6, exon 4, exon 11, and exon 12, most PSEN2 variants in exon 5, and exon 7, and most APP variants in exon 14, exon 16, exon 17, which was consistent with previous studies (Raux et al, 2005;Barber et al, 2016). In the Asain population, variants in exon 4, exon 7, exon 11, exon 14, and exon 17 of the APP, exon 4, exon 5, exon 6, exon 7, exon 8, and exon 12 of the PSEN1, as well as exon 5, exon 6, and exon 7 of the PSEN2 gene were discovered between 2009 and 2018 (Giau et al, 2019). In the French population, PSEN1 variants are located in exon 4, exon 5, exon 6, exon 7, exon 8, exon 9, exon 10, exon 11, and exon 12.…”
Section: Discussionsupporting
confidence: 91%
“…Our re-analysis found that most PSEN1 variants are located in exon 7, exon 5, exon 8, exon 6, exon 4, exon 11, and exon 12, most PSEN2 variants in exon 5, and exon 7, and most APP variants in exon 14, exon 16, exon 17, which was consistent with previous studies (Raux et al, 2005;Barber et al, 2016). In the Asain population, variants in exon 4, exon 7, exon 11, exon 14, and exon 17 of the APP, exon 4, exon 5, exon 6, exon 7, exon 8, and exon 12 of the PSEN1, as well as exon 5, exon 6, and exon 7 of the PSEN2 gene were discovered between 2009 and 2018 (Giau et al, 2019). In the French population, PSEN1 variants are located in exon 4, exon 5, exon 6, exon 7, exon 8, exon 9, exon 10, exon 11, and exon 12.…”
Section: Discussionsupporting
confidence: 91%
“…Although enormous efforts have been made by many researchers, currently there are no effective disease-modifying therapies available. Mutations of the amyloid precursor and some external factors, such as heating, create large challenges for the treatment of amyloidosis [43,44]. At present, some proposals and research involve treatments for amyloidosis based on antibodies, metal ions, and RNA interference, but none have been certified as medicine for amyloidosis therapy and applied clinically [17,[45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Over 300 mutations in PSEN1 have been reported in the literature, in which close to 270 were pathogenic. Until 2019, 57 mutations of PSEN1 were discovered in Asian countries, including Japan, Korea, the People’s Republic of China, Iran and Thailand 34 . A recently published systemic review disclosed that a PSEN1 mutation was found in 66.7% of Chinese FAD and 72.7% of Asian (Chinese, Korean, and Japanese) FAD families 35 .…”
Section: Discussionmentioning
confidence: 99%